THEORETICAL FOUNDATIONS AND SIGNIFICANCE OF MEMORY IN ENGLISH LANGUAGE TEACHING (Universal International Scientific Journal, 2026)
Memory plays a central role in the process of learning a foreign language,particularly in English language teaching (ELT), where learners are required to acquire, store, retain,and retrieve large amounts of linguistic information. This article examines the theoretical foundationsof memory from the perspectives of cognitive psychology and applied linguistics and explores theirrelevance to English language teaching. The study analyzes key memory models, including short-termmemory, long-term memory, and working memory, and discusses their impact on vocabularyacquisition, grammar learning, and speaking fluency. Special attention is given to memory-relatedprocesses such as encoding, retention, and retrieval, which significantly influence language learningoutcomes. The article also highlights the pedagogical implications of memory theories for classroompractice, emphasizing memory-based teaching strategies that enhance learners’ cognitive engagementand long-term language retention.
Keywords: memory; working memory; English language teaching